20, 000 picometers under the OMM: diving into the vastness of mitochondrial metabolite transport. (23rd April 2020) - Cunningham, Corey N; Rutter, Jared
Abstract: The metabolic compartmentalization enabled by mitochondria is key feature of many cellular processes such as energy conversion to ATP production, redox balance, and the biosynthesis of heme, urea, nucleotides, lipids, and others. For a majority of these functions, metabolites need to be transported across the impermeable inner mitochondrial membrane by dedicated carrier proteins. Here, we examine the substrates, structural features, and human health implications of four mitochondrial metabolite carrier families: the SLC25A family, the mitochondrial ABCB transporters, the mitochondrial pyruvate carrier (MPC), and the sideroflexin proteins. Abstract : Mitochondrial carriers play an essential role in the metabolic compartmentalization by mitochondria. This review discusses the substrates, structural features, and human health implications of mitochondrial metabolite carriers.